Estimation of Factors for Standardizing Lactations to Mature Equivalent of Simmental Cattle - Kaygisiz, A; Şahin, O; Yılmaz, İ (Journal of the Hellenic Veterinary Medical Society, 2025)
In this study, correction factors which will use mature age equivalent in Turkish Simmental cattle population were determined. Across the country, 59247 lactation milk yield records of 28971 head of cows between 1990 and 2023 were used. Correction coefficients for milk yield according to maturity age were calculated by taking into account 22 different age groups and 4 seasonal groups. Cows calving in spring, summer, autumn and winter reached their adult milk yield of 305 days at 64-66 months, 52-54 months, 58-60 and 37-39 months, respectively. Accordingly, the current results show that cows calving in autumn and winter reach mature age for 305-day milk yield earlier than those calving in spring and summer seasons.